Association of Concave Deformity of the Anterior Scalene on Magnetic Resonance Imaging with Vascular Variant of Neurogenic Thoracic Outlet Syndrome - Madi El-Haj, MD, MS; Shaul Beyth, MD; Amit Korach, MD; Ori Wald, MD; Tal Eliav, MS; Yosef Kalish, MD; Sofia A. Vorobeitchik, MS; Allan I. Bloom, MD (Plastic and Reconstructive Surgery, Global Open, 2024)
Background:. Neurogenic thoracic outlet syndrome (NTOS) is a dynamic compression of the brachial plexus. This study aimed to evaluate the correlation between the concave deformity of the posterior edge of the anterior scalene muscle (CDAS) on sagittal T1 with intraoperative findings of vascular compression. The second aim was to define the NTOS vascular subtypes and establish possible treatments. Methods:. We retrospectively reviewed patients who met the Consortium for Research and Education on Thoracic Outlet Syndrome criteria for NTOS and were operated on after a failed rehabilitation program. Results:. Forty-four patients were included; mean age was 29.51 years (range: 13–55 years), and 24 (54.5%) were women. CDAS on sagittal T1 magnetic resonance imaging (MRI) was identified in 20 of 44. Patients were divided into two categories: type A (pure NTOS) (20 of 44); and type B (mixed neurogenic-vascular variants) (24 of 44). Type B was divided into B1, B2, and B3, corresponding to subclavian artery (SCA) compression (seven of 44), subclavian vein compression (SCV) (five of 44), and both SCA and SCV compression (12 of 44), respectively. All patients with B1 had CDAS on MRI T1 sagittal, whereas CDAS was found on 5%, 60%, and 58.3% in types A, B2, and B3, respectively. Intraoperatively, all patients had at least one structural anomaly. Preoperative symptoms of lower or middle-lower brachial plexus trunk compressions were more prominent in patients with the vascular variant (B1: 85%, B2: 83%, and B3: 83%) than the pure NTOS (type A) (40%). Conclusions:. NTOS presents as four subtypes: pure neurogenic (A) and vascular (B1, B2, and B3). Preoperative middle/lower trunk symptoms combined with positive upper limb duplex ultrasound of the SCA, SCV, and sagittal MRI show that a CDAS is correlated with the vascular form of NTOS and predicts failure of preoperative rehabilitation program.